Does Zn mimic diffusion of Al in the HCP Al-Sc-Hf-Ti-Zr high entropy alloys?. (May 2023) - Sen, Sandipan; Zhang, Xi; Rogal, Lukasz; Wilde, Gerhard; Grabowski, Blazej; Divinski, Sergiy V.
Abstract: The presence of Al in the hexagonal close-packed (HCP) Al-Sc-Hf-Ti-Zr high-entropy-alloy system was previously found to be a primary reason for partial D019 ordering. Since tracer measurements of Al self-diffusion are extremely challenging due to the absence of a suitable radioisotope, in this work, diffusion of Zn as a solute element is investigated for two HCP Al-Sc-Hf-Ti-Zr alloys. The experimental results on diffusion of the 65 Zn radioisotope are benchmarked against Al diffusion rates predicted by kinetic Monte Carlo simulations using ab initio -informed calculations of the vacancy formation and migration energies. Furthermore, the partitioning of Zn and the mechanism of Zn diffusion are evaluated. Similarities between Zn and Al diffusion in the investigated HCP Al-Sc-Hf-Ti-Zr alloys are traced back to correlations between the corresponding chemically resolved site substitution energies and migration barriers. Graphical abstract: